Penggunaan Gaya Bahasa Calon Presiden Dalam Video Debat Capres Republik Indonesia Pada Pemilihan Umum 2024 Di Channel You Tube Kompas Tv - Widiatmoko, Arief; Khermarinah, Khermarinah; Wediasti, Welti (Lembaga Riset dan Inovasi Almatani, 2024)
In this research the author used a qualitative descriptive method. The method used is to explain the data using an analysis system and detail all forms of research results clearly. The data in this research is the use of language styles by each presidential candidate during the debate. The data source was obtained from the YouTube video of the third presidential candidate debate in the 2024 general election. There are 2 uses of comparative language styles, namely the metanomia figure of speech used once, the figure of speech simile used once. The 7 uses of satirical language styles are that there are four uses of the cynicism figure of speech, the iunenndo figure of speech once, and the satire figure of speech three times. There are 3 uses of affirmative language styles, namely repetition figures of speech four times. Ganajar Pranowo, presidential candidate number 03, uses 6 uses of language styles, there are 2 uses of comparative language styles, namely one use of metonomia figure of speech, one use of euphemism figures of speech. There are 4 uses of satirical language styles, namely two uses of the cynicism figure of speech and two uses of the iunenndo figure of speech.